Aggregation-induced chirality amplification of optically active fluorescent polyurethane and a cyclic dimer in the ground and excited states. Issue 7 (24th December 2021) - Song, Zhiyi; Sato, Hiroyasu; Pietropaolo, Adriana; Wang, Qingyu; Shimoda, Shuhei; Dai, Heshuang; Imai, Yoshitane; Toda, Hayato; Harada, Takunori; Shichibu, Yukatsu; Konishi, Katsuaki; Bando, Masayoshi; et al.
Abstract : A helical polyurethane composed of alternating fluorene-2, 7-diyl and 1, 1′-binaphthyl-2, 2′-diyl units showed intense CD and the corresponding cyclic dimer exhibited circularly polarized light emission with high anisotropy through aggregation-induced chirality amplification. Abstract : Optically active linear polyurethane and a cyclic dimer were synthesized from 2, 7-diisocyanatofluorene and 2, 2′-dihydroxy-1, 1′-binaphthyl. The circular dichroism (CD) spectral intensity of the polymer was amplified at a higher concentration through aggregate formation, while circularly polarized light (CPL) emission was not enhanced. The cyclic dimer's CPL emission was largely amplified ( g lum 1.1 × 10 −2 ) due to intermolecular excimer formation through aggregation, while the CD intensity was not affected.